2010
DOI: 10.1007/s11244-010-9595-4
|View full text |Cite
|
Sign up to set email alerts
|

The Uses and Challenges of Zeolites in Automotive Applications

Abstract: This study gives an overview of zeolites used for hydrocarbon trapping, selective catalytic reduction of nitrogen oxides (NO x ) with NH 3 (NH 3 -SCR) and hydrocarbon NO x reduction applications. We also discuss challenges for the use of zeolites in these applications and the material properties that require improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…As it has been previously reported [27], there is a significant effect of copper loading on the reducibility of the different copper species. From our data, it can be confirmed that an increase of the copper loading shifts the reduction peaks to lower temperature [15], due to the formation of dimeric copper species as the copper loading increases [28].…”
Section: Catalyst Characterizationsupporting
confidence: 66%
“…As it has been previously reported [27], there is a significant effect of copper loading on the reducibility of the different copper species. From our data, it can be confirmed that an increase of the copper loading shifts the reduction peaks to lower temperature [15], due to the formation of dimeric copper species as the copper loading increases [28].…”
Section: Catalyst Characterizationsupporting
confidence: 66%
“…In particular, controlling NO x emission from a diesel-engine automobile, which is expected to show high combustion efficiency toward CO 2 reduction, 1 is critical because of stringent regulations like EURO 6 and US 10. 2 As a result of the lean-burning conditions in diesel engines, it is difficult to remove NO x using the conventional three-way catalyst installed on gasoline engines. A selective catalytic reduction (SCR) system using urea, which is served as a source of ammonia (NH 3 ) as a reductant, has been widely applied to remove NO x under oxidizing conditions.…”
mentioning
confidence: 99%
“…This is particularly challenging for copper exchanged zeolites that typically loose more catalytic NH 3 -SCR activity than their iron equivalents under hydrothermal conditions. [68]. As shown in Chapter 2 and recently reported by Fickel et al small-pore zeolites show superior hydrothermal stability compared to other zeolites.…”
Section: Introductionmentioning
confidence: 69%
“…For the abatement of NO x using copper zeolites, by far most literature data is available for Cu-MFI, Cu-BEA, Cu-FAU, Cu-MOR and Cu-FER. [16][17][18][19][20][21][22][23][24][25][26][27] Over the years less common topologies, which are not commercially available, have also been studied as potential candidates for the SCR reaction, [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation